The Collaboration Practice of Health Interprofessionals in Infertility Service: Scoping Review - Vika Tri Zelharsandy and Sulistyaningsih (International Journal of Advanced Science and Technology, 2020)
Infertility problem increases around the world included developed countries. The role of health interprofessional is extremely important in decreasing the infertility number until it needs to conduct collaboration practice of health interprofessional in giving infertility service. The purpose of this study is to know collaboration practice of health interprofessional on infertility service. Article identification useed Database PubMed, ProQuest, Wiley, Science Direct and grey literature (Google Scholar) from 2009 until 2019. Out of 80 articles, nine articles were obtained based inclusion and exclusion criteria. This research was qualitative with mix methods. The articles obtained from advance countries consisted of 1 Osaka article, 1 Netherland article, 1 Belgium article, 1 England article, 1 Oxford article, 1 Canada article, 1 New York article, 1 Australia article, and developed countries consisted of 1 Iran article. There are two findings related to collaboration practice such as the role and inhibition of interprofessional collaboration practice in infertility service. In giving infertility service, collaboration practice of health interprofessional is needed to overcome the inhibitions occured.